DESCRIPTION OF SYNTACTIC-COMPOSITIONAL PARTS OF SPEECH (Scientific journal of the Fergana State University, 2023)
The article deals with the units that play an important role in the formation of speech, the study of compositional-syntactic structure, its semantic-structural and functional evaluation, the components that make it up in a particular space and time, syntactic-stylistic figures, sentences and more. orderly arrangement of image-forming means, syntactic-compositional parts interpreted as logical and linguistic categories, reference, subject definition, reminder, description, proof, rejection, claim, conclusion, word, compound, sentence, phrase, methodological means, linguistic categories, subject, title, title, epigraphy, written speech, text, poetic speech, introduction to a single supersyntactic, lyroepic works, the system of linguistic and verbal means of expression and their main features, beginning as compositional parts orderly positioning, “scattered”, consistent development, flow of thought, and completion.